2014
DOI: 10.1063/1.4863444
|View full text |Cite
|
Sign up to set email alerts
|

Charge/mass dynamic structure factors of water and applications to dielectric friction and electroacoustic conversion

Abstract: We determine time correlation functions and dynamic structure factors of the number and charge density of liquid water from molecular dynamics simulations. Using these correlation functions we consider dielectric friction and electro-acoustic coupling effects via linear response theory. From charge-charge correlations, the drag force on a moving point charge is derived and found to be maximal at a velocity of around 300 m/s. Strong deviations in the resulting friction coefficients from approximate theory emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…between fluctuations in mass density and fluctuations in charge density. 56 The large spatial range and coherent propagation of these modes is surprising and implies the existence of an extended hydrogen bond network, in contrast to earlier ideas about the structure of water which emphasize dynamics as being confined within small clusters. 57 Simulations with larger simulation boxes are needed to fully quantify the extent of the longitudinal modes.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…between fluctuations in mass density and fluctuations in charge density. 56 The large spatial range and coherent propagation of these modes is surprising and implies the existence of an extended hydrogen bond network, in contrast to earlier ideas about the structure of water which emphasize dynamics as being confined within small clusters. 57 Simulations with larger simulation boxes are needed to fully quantify the extent of the longitudinal modes.…”
Section: Discussionmentioning
confidence: 83%
“…However, normal mode analysis of liquid water and clusters shows that the H-bond stretching modes have a wide distribution of frequencies, which overlaps with the librational modes, so some coupling between these modes is possible 54 55 . Recently, it was shown that there is coupling between the acoustic and optic modes in water—that is, between fluctuations in mass density and fluctuations in charge density 56 .…”
Section: Discussionmentioning
confidence: 99%
“…al. [39]. For small perturbations, the response of a medium to an electric field takes a linear form…”
Section: Dielectric Responsementioning
confidence: 99%
“…where P is the polarization of the medium, D is the electric displacement field, and where the dynamic structure factor can be written have been studied for multiple water models in different contexts [39]. In addition to the charge-charge autocorrelation function, we will also consider the force-force autocorrelation function, which is related to the friction coefficient [62].…”
Section: Dielectric Responsementioning
confidence: 99%
See 1 more Smart Citation